2011
DOI: 10.1007/s10529-011-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of GDP-mannose using coupling fermentation of recombinant Escherichia coli

Abstract: Glucokinase (glk), phosphomannomutase (manB), and mannose-1-phosphate guanylytransferase (manC) are needed for the biosynthesis of GDP-mannose. A recombinant E. coli strain over-expressing these three genes was constructed to produce guanosine 5'-diphosphate (GDP)-mannose, the donor of GDP-fucose, an essential substrate for synthesis of fucosyloligosaccharides. In addition, the glk, manB, and manC genes were individually cloned into the expression vector pET-22b (+) to construct three recombinant E. coli strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The GDP‐Man synthesized within 72 h (581 mg) was isolated in 34.3% yield. Using a similar one‐pot approach, however, applying instead of purified HK, PMM and ManC whole cells of E. coli , each expressing one of the three enzymes recombinantly, Honghong et al demonstrated formation of GDP‐Man (21 mM; 680 mg) from Man (65 mM) and an energy source ( d ‐fructose, 130 mM) within 22 h. The product was not isolated though.…”
Section: Introductionmentioning
confidence: 99%
“…The GDP‐Man synthesized within 72 h (581 mg) was isolated in 34.3% yield. Using a similar one‐pot approach, however, applying instead of purified HK, PMM and ManC whole cells of E. coli , each expressing one of the three enzymes recombinantly, Honghong et al demonstrated formation of GDP‐Man (21 mM; 680 mg) from Man (65 mM) and an energy source ( d ‐fructose, 130 mM) within 22 h. The product was not isolated though.…”
Section: Introductionmentioning
confidence: 99%